THE DEVELOPMENT OF THE PASAR KEPUH IN KUNINGAN DISTRICT - Dinni Fitri Fadilah; Saihul Anwar (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2020)
Development is an attempt to develop an effective product for future use. And when it is associated with Development education means a gradual process of change in the direction of a higher and more widespread that can thoroughly create a perfection or maturity.The market is an economic institution where buyers and sellers meet, both directly and indirectly in the form of shopping centers, public markets, shops, malls, plazas, trade centers and other designations, to conduct trade transactionsThe method used in this Thesis is to use qualitative methods, namely by emphasizing Primary and Secondary Data, Analysis Of The Projected Number Of Traders, Analysis Of Market Area Development uses the SWOT method, Analysis Of Extensive Building Needs, Calculation Of Parking Land Needs, Planning Waste Management System, Calculation Of Drainage, Design Of Market and Analysis Of Engineering Economic.The conclusion taken from The Development Of Pasar Kepuh is Pasar Kepuh will developed into a Semi-Modern Market by maintaining land area which is 27,161 m2 and will developed into 3 floors with a total building area of 30.315,68 m2. The number of kiosks of 1356 units and 416 units for stall. Pasar Kepuh development project after 25 years will be reater, Rp. 61.200.000.000 so to equalize the present value of future value with the present value of the expenditure for invesement requires interest 16,78%.